Clinicopathological classification of immune checkpoint inhibitor-associated myocarditis: possible refinement by measuring macrophage abundance - Jesus Jimenez; Nicolas Kostelecky; Joshua D. Mitchell; Kathleen W. Zhang; Chieh-Yu Lin; Daniel J. Lenihan; Kory J. Lavine (Cardio-Oncology, 2023)
Abstract Background Immune checkpoint inhibitor (ICI) myocarditis is associated with high morbidity and mortality. While endomyocardial biopsy (EMB) is considered a gold standard for diagnosis, the sensitivity of EMB is not well defined. Additionally, the pathological features that correlate with the clinical diagnosis of ICI-associated myocarditis remain incompletely understood. Methods We retrospectively identified and reviewed the clinicopathological features of 26 patients with suspected ICI-associated myocarditis based on institutional major and minor criteria. Seventeen of these patients underwent EMB, and the histopathological features were assessed by routine hematoxylin and eosin (H&E) staining and immunohistochemical (IHC) staining for CD68, a macrophage marker. Results Only 2/17 EMBs obtained from patients with suspected ICI myocarditis satisfied the Dallas criteria. Supplemental IHC staining and quantification of CD68+ macrophages identified an additional 7 patients with pathological features of myocardial inflammation (> 50 CD68+ cells/HPF). Macrophage abundance positively correlated with serum Troponin I (P = 0.010) and NT-proBNP (N-terminal pro-brain natriuretic peptide, P = 0.047) concentration. Inclusion of CD68 IHC could have potentially changed the certainty of the diagnosis of ICI-associated myocarditis to definite in 6/17 cases. Conclusions While the Dallas criteria can identify a subset of ICI-associated myocarditis patients, quantification of macrophage abundance may expand the diagnostic role of EMB. Failure to meet the traditional Dallas Criteria should not exclude the diagnosis of myocarditis.